Avaliação do risco de fratura osteoporótica e indicação de tratamento baseado no FRAX e diretriz do NOGG na população de idosos da cidade de Canhoba – Sergipe - Mesquita, Yan Thieris Santos (2019)
OBJECTIVE: Evaluate the risk for osteoporotic fracture and indication of treatment through the FRAX tool and NOGG in the elderly. METHODS: This is a descriptive, observational and cross-sectional study with quantitative approach and convenience sampling with 133 elderly individuals living in the city of Canhoba, municipality of Sergipe state. The data collection instrument used was a questionnaire structured and specially developed for this study that addresses demographic data, risk factors for osteoporosis and osteoporotic fracture. RESULTS: There was a female predominance (54%). In the FRAX analysis, 2.2% of the eligible sample presented a higher fracture risk and a 36.8% risk of hip fracture. In the analysis by means of NOGG, 90.2%, 9% and 0.7% of the elderly presented low, medium and high risk for fracture, respectively. Of the 48 subjects who would receive specific medical treatment according to FRAX only one would receive osteoporosis medication, 12 would require investigation with bone densitometry (DXA) and 35 only follow-up with clinical reassessment, if necessary. CONCLUSION: Our data demonstrate that risk factors for osteoporosis and for osteoporotic fracture are prevalent in the elderly population. To evaluate the risk of major fracture and hip fracture and indication of treatment using FRAX and NOGG, we showed that there was a difference in the reduction of the indication of treatment through the NOGG tool.